Epilepsia extratemporal. Selección del candidato y tratamiento quirúrgico - Pomata, Hugo B. (Revista Argentina de Neurocirugía, 2021)
We analyzed the outcome in 60 children and 8 adults with extratemporal epilepsy operated between 1988-1998 and a follow-up of more than 2 years. AU patients were studied with CAT, MRI and scalp EEG. Video-telemetry, intraoperative ECoG and SSEP were used according to the needs of each case. In children were performed 24 lesionectomies, 25 disconnections, 7 polectomies and/ Or lobectomies, 1 hemispherectomy and 3 corticectomies. In the adults we performed 1 lobectomy, 4 corticectomies and 3 lesionectomies. According with Engercriteria, the surgical results in children were: 40 class I, 5 class II and 4 class N. In the adults the surgical results were: 4 class I, 2 class II, 1 class III and 1 class IV We excluded 11 patients with callostomies because Engel'criteria could not be applied.
Keywords: extratemporal epilepsy; surgery